Secondary school students' perceptions of working life skills in science-related careers. Issue 10 (3rd July 2017) - Salonen, Anssi; Hartikainen-Ahia, Anu; Hense, Jonathan; Scheersoi, Annette; Keinonen, Tuula
ABSTRACT: School students demonstrate a lack of interest in choosing science studies and science-related careers. To better understand the underlying reasons, this study aims to examine secondary school students' perceptions of working life skills and how these perceptions relate to the skills of the twenty-first century. The participants in this study were 144 Finnish 7th graders (aged 13–14 years). Using a questionnaire and qualitative content analysis, we examined their perceptions of working life skills in 'careers in science' and 'careers with science'. Results reveal that although students have a great deal of knowledge about working life skills, it is often just stereotyped. Sector-specific knowledge and skills were highlighted in particular but skills related to society, organisation, time and higher order thinking, were often omitted. Results also indicate that students do not associate 'careers in science' with creativity, innovation, collaboration or technology and ICT skills. Conversely, according to the students, these careers demand more sector-specific knowledge and responsibility than 'careers with science'. We conclude that students need more wide-ranging information about scientific careers and the competencies demanded; such information can be acquired by e.g. interacting with professionals and their real working life problems.